1985
DOI: 10.1021/bi00346a016
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics and thermodynamics of calcium-induced lateral phase separations in phosphatidic acid-containing bilayers

Abstract: The effects of calcium on the mixing of synthetic diacylphosphatidylcholines (PC's) and diacylphosphatidylethanolamines (PE's) with the corresponding phosphatidic acids (PA's) have been examined by high-sensitivity differential scanning calorimetry and by measurements of the fluorescence of labeled PA or PC species in PA-PC bilayers. Calorimetrically derived phase diagrams for dimyristoyl- and dielaidoyl-substituted PA-PC and PA-PE mixtures indicate that these species are readily miscible in the absence of cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

20
59
1

Year Published

1986
1986
2008
2008

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 88 publications
(80 citation statements)
references
References 24 publications
(44 reference statements)
20
59
1
Order By: Relevance
“…Representative thermograms for mixtures of DEPC and DEPA in the presence of high magnesium levels are shown in Figure 7A. The thermograms are qualitatively very similar to those observed previously for this lipid system in the presence of high levels of calcium (Graham et al, 1985), and they can be analyzed in an entirely similar way to give the phase diagram shown in Figure 7B. For the purposes of the present discussion, the most important feature of this phase diagram is the lefthand vertical boundary of the two-phase region existing between 22 and 94 "C, since this boundary defines the bilayer concentration of DEPA below which no phase separation will occur in the presence of magnesium.…”
Section: Relationship Of Fusion To Pa-pc Phase Separationsupporting
confidence: 84%
See 3 more Smart Citations
“…Representative thermograms for mixtures of DEPC and DEPA in the presence of high magnesium levels are shown in Figure 7A. The thermograms are qualitatively very similar to those observed previously for this lipid system in the presence of high levels of calcium (Graham et al, 1985), and they can be analyzed in an entirely similar way to give the phase diagram shown in Figure 7B. For the purposes of the present discussion, the most important feature of this phase diagram is the lefthand vertical boundary of the two-phase region existing between 22 and 94 "C, since this boundary defines the bilayer concentration of DEPA below which no phase separation will occur in the presence of magnesium.…”
Section: Relationship Of Fusion To Pa-pc Phase Separationsupporting
confidence: 84%
“…we investigated the possibility that such fusion requires the lateral segregation of PA-enriched domains in the vesicle membranes. In a previous study (Graham et al, 1985). Aggregates of vesicles can be observed, and many bilamellar diaphragms can be observed in these aggregates in regions of extensive intervesicle contact, as Rand et al (1985) have reported previously for phosphatidylserine vesicles treated with calcium.…”
Section: Relationship Of Fusion To Pa-pc Phase Separationsupporting
confidence: 72%
See 2 more Smart Citations
“…The fluorescence of NBD-labeled phospholipids is subject to self-quenching, providing a basis for detecting phospholipid association in the membrane (30,31). Using this property, we tested the possibility that signal peptides induce phase separation of acidic phospholipid.…”
Section: Lateral Segregation Of Phosphatidylglycerol Induced By Signamentioning
confidence: 99%